1993
DOI: 10.1111/j.1469-8137.1993.tb03819.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological plasticity of the clonal herb Lamiastrum galeobdolon (L.) Ehrend. & Polatschek in response to partial shading

Abstract: SUMMARYThe present experiment investigates the morphological plasticity of Lamiastrum galeobdolon (L.) Ehrend. & Polatschek in response to light patchiness. In a garden experiment, stolons of the plant were grown under the following six light regimes: high light, low light, from low light to high light, from high light to low light, under high light but with the apical region of the stolon under low light, and under low light but with the apical region under high light. The low-light conditions provided 50% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 28 publications
5
36
0
Order By: Relevance
“…Clonal plants may respond to variation in environmental factors by plastic adjustment of their morphology (Slade & Hutchings 1987a, b;de Kroon & Knops 1990;Evans 1992;Caradus et al 1993;Dong 1993;Thompson 1993;Dong & de Kroon 1994;Hutchings & de Kroon 1994). Morphological plasticity in spacer (rhizome, stolon internode, Bell 1984) characters such as branching probability and length as well as in ramet characters such as leaf area and ramet height may be of ecological significance.…”
Section: Introductionmentioning
confidence: 99%
“…Clonal plants may respond to variation in environmental factors by plastic adjustment of their morphology (Slade & Hutchings 1987a, b;de Kroon & Knops 1990;Evans 1992;Caradus et al 1993;Dong 1993;Thompson 1993;Dong & de Kroon 1994;Hutchings & de Kroon 1994). Morphological plasticity in spacer (rhizome, stolon internode, Bell 1984) characters such as branching probability and length as well as in ramet characters such as leaf area and ramet height may be of ecological significance.…”
Section: Introductionmentioning
confidence: 99%
“…Even if plants are always sampled from unshaded habitats, it is hard to control for the effects of self-shading. This could potentially have very large effects, because sun and shade leaves on the same plant might differ in SLA by a factor of two (Popma & Bongers, 1988 ;Cornelissen, 1992 ;Dong, 1993). Shipley & Meziane (1998) have shown that both mineral nutrition and irradiance can have complex and interactive effects on SLA.…”
Section: mentioning
confidence: 99%
“…We attempted to provide light conditions to the target clover in a manner that was more natural than in previous studies (e.g. Solangaarachchi and Harper 1987;Thompson and Harper 1988;Ballare et al 1990Ballare et al , 1992Novoplansky et al 1990;Dong 1993;Ballare 1994;Leeflang 1999). This was done by exposing the white clover to light reflected from living grass neighbours, and to light filtered through grass neighbours, yet allowing the clover to receive large patches of unfiltered light.…”
Section: Introductionmentioning
confidence: 98%
“…Morphological adjustment to changing light conditions has been reported for some stoloniferous species such as Eichhornia crassipes (Méthy et al 1990), Veronica spp. (Dale and Causton 1992), Lamiastrum galeobdolon (Dong 1993;Leeflang 1999), Trifolium repens (Barthram 1997;Gautier et al 1998) and Potentilla spp. (Stuefer and Huber 1998).…”
Section: Introductionmentioning
confidence: 99%